2018
DOI: 10.3390/en11061584
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement of TiO2/Water Nanofluid at Laminar and Turbulent Flows: A Numerical Approach for Evaluating the Effect of Nanoparticle Loadings

Abstract: Titania-based nanofluid flowing inside a circular tube under the boundary condition of a horizontal uniformly heated wall was investigated numerically for both laminar and turbulent flows. In this work, an innovative numerical method using an Eulerian approach for the two-phase mixture model was used to simulate the flow and convective heat transfer characteristics. The effect of nanoparticle loading and Reynolds number on the flow and heat transfer characteristics was observed. The Reynolds number was 500 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
3
25
0
3
Order By: Relevance
“…To solve the Equations (13) to (14), we guess the values of y 3 , y 5 which are not given at the initial conditions. All initial conditions are obtained, and Equations (13) to (14) are resolved and integrated by utilizing RKF with the consecutive iterative process.…”
Section: Numerical Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve the Equations (13) to (14), we guess the values of y 3 , y 5 which are not given at the initial conditions. All initial conditions are obtained, and Equations (13) to (14) are resolved and integrated by utilizing RKF with the consecutive iterative process.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…Ashorynejad and Zarghami reported the MHD flow of Cu‐water nanofluid through a porous channel. Afterward, voluminous theoretical and experimental exertions were established to scrutinize the diverse aspects of nanofluids (see Parsaiemehr et al) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, for an intensification of heat transfer within different engineering systmes the nanosized metal or metal oxide particles are used [11][12][13]. Different experimental studies showed that an inclusion of nanoparticles of low concentration can improve the heat transfer performance inside the system [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, Choi [56] presented the scientific community with the concept of nanofluids, and the discovery was revolutionary. Over the years, nanofluids attracted many scientists from all over the world, who started to test them in wide-ranging applications [57][58][59][60][61][62][63]. Therefore, the use of nanofluids seems to be very promising in enhancing the thermal conductivity of a base fluid, but attention must be paid to the synthesis and the characterizations of them.…”
mentioning
confidence: 99%